2019
DOI: 10.1093/hmg/ddz144
|View full text |Cite
|
Sign up to set email alerts
|

Transcription of PIK3CD in human brain and schizophrenia: regulation by proinflammatory cytokines

Abstract: PIK3CD encodes the phosphoinositide 3-kinase (PI3K) catalytic subunit, p110δ, a lipid kinase linked to neurodevelopmental disorders, including schizophrenia (SZ). PIK3CD is regulated at the transcript level through alternate use of 5' untranslated exons (UTRs), promoters, and proinflammatory cytokines. Increases in global PIK3CD expression and downregulation by neuroleptics are observed in SZ, and preclinical efficacy of a p110δ-selective inhibitor is seen in rodent models of risk. Here, we cloned PIK3CD alter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 45 publications
1
12
0
Order By: Relevance
“…In the p110δ E1020K murine model, we detected more subtle phenotypic alterations. Consistent with this hypothesis, recent studies found more PIK3CD transcripts in human foetal brain than in adult samples (18) and distributed expression of PIK3CD in the developing mouse brain (66). Combined with the fact that PI3Kδ lies upstream of the mTOR pathway, a signalling hub that is highly active during brain development and often found to be dysregulated in neurodevelopmental disorders (19,67,68), this expression suggests that PIK3CD plays a still unexplored role in the modulation of brain development, adding to the growing body of evidence pointing to a critical period for ASD development (52,69).…”
Section: Discussionsupporting
confidence: 56%
“…In the p110δ E1020K murine model, we detected more subtle phenotypic alterations. Consistent with this hypothesis, recent studies found more PIK3CD transcripts in human foetal brain than in adult samples (18) and distributed expression of PIK3CD in the developing mouse brain (66). Combined with the fact that PI3Kδ lies upstream of the mTOR pathway, a signalling hub that is highly active during brain development and often found to be dysregulated in neurodevelopmental disorders (19,67,68), this expression suggests that PIK3CD plays a still unexplored role in the modulation of brain development, adding to the growing body of evidence pointing to a critical period for ASD development (52,69).…”
Section: Discussionsupporting
confidence: 56%
“…Phosphoinositide 3-kinases (PI3Ks) are modulators of cellular membrane lipids involved in signaling and trafficking events. In the brain, PI3K␦ is expressed in neurons and microglia (Eickholt et al, 2007;Low et al, 2014;Hood et al, 2019). Despite its established role in controlling functions in autoimmunity and inflammation (Okkenhaug and Vanhaesebroeck, 2003;Ali et al, 2014), the role of PI3K␦ in neurons remains largely unknown, with the effects of inhibiting this isoform in the context of neurological disorders also remaining unexplored.…”
Section: Introductionmentioning
confidence: 99%
“…PI3K signaling is essential for a wide range of neurobiological functions, with an emerging focus on the individual roles of PIK3 catalytic subunits in disorders of neurodevelopment (Gross and Bassell, 2014). Specifically, the Class I PIK3 catalytic subunit p110δ has drawn attention for the genetic association to psychiatric disorders, increased expression in schizophrenia, autism and intellectual delay, as well as an emerging novel target for antipsychotic drug development (Marder et al, 2011;Law et al, 2012;Rico, 2012;Papaleo et al, 2016;Poopal et al, 2016;Coulter et al, 2017;Hood et al, 2019). While the neuronal consequences of p110δ inhibition have begun to be addressed, the impact of clinically-relevant overexpression of p110δ has not been explored.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies suggest that the PIK3CD/p110δ catalytic subunit is one such isoform relevant for neurological development and disease, with PIK3CD being associated with increased risk for schizophrenia (Law et al, 2012), and increased expression being identified in patients with schizophrenia or autism spectrum disorder (Law et al, 2012;Poopal et al, 2016;Hood et al, 2019). Moreover, patients carrying gain-of-function mutations in the PIK3CD gene, termed ''activated PI3K-δ syndrome,'' are often diagnosed with intellectual delay (Coulter et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation